Digital Transformation Strategy For Non-Government Organization (Case Study: Inisiatif Zakat Indonesia) - Mohammad Luqmanul Hakim; Aisyah Nurlita Utami; Hanifa Fissalma (Jurnal Indonesia Sosial Teknologi, 2023)
Zakat is a philanthropic activity Zakat is a philanthropic activity with huge prospects and usage, yet there is a significant gap between its economic potential and its actualization; according to BAZNAS, in 2020 Indonesia's zakat fund only utilized 4.3% of its potential. Moreover, the majority of Zakat funds are acquired through conventional channels; in 2019, only 13% of IZI's total Zakat funds came from digital channels, while 87% came from traditional channels. One of the reasons for this is that muzak (people who must pay zakat) are not proficient in using digital platforms, and the community is unaware of exactly what to do. Also, when it comes to collecting zakat funds, their administration and distribution to ashraf or mustahik (those who qualify to receive zakat funds), their accurate distribution, and staff members not using digital tools. The objective of this study is to find answers that will help us figure out what the Zakat IZI management system needs to accomplish to become digitally transformed and how it can be improved and gained. This research is a case study with qualitative methods. We collect data for this study using a variety of methods, such as interviews, literature reviews, and document analysis.